Sistemas para inserção de potência ativa e compensação de tensão integrados via inversor de nove chaves - Assis, Jefferson Rafael Pereira de (2021)
This work presents an analysis of the operation of a nine-switch three-phase voltage inverter (NSI - Nine-Switch Inverter) designed as an integration of a system to insert power into the grid with a Dynamic Voltage Restorer (DVR), as well as a control system and modulation scheme suitable for this purpose. The use of a nine-switch three-phase voltage inverter is able to unite the power insertion function in the network and DVR in a single system, according to the necessary number of switches from nine to nine, which allows reducing the cost of the system and maintaining as two features. The modulation scheme used, the control system and all modes of operation of the integrated system are discussed and its operation is analyzed through simulation using the Simulink / MATLAB software. The validation of the presented system is performed through real-time simulations in the OP5700 simulator from OPAL-RT Technologies.